POLA DISTRIBUSI HUJAN JAM-JAMAN DAERAH MANADO, MINAHASA UTARA DAN MINAHASA - Sumarauw, Jeffry S. F. (JURNAL SIPIL STATIK, 2017)
Design rainfall is an input for analyzing the ungagged cathment design flood. Daily rainfall should be transformed into hourly rainfall. Transforming the daily rainfall to hourly rainfall by using the Storm Pattern of each own area. Until now there is no research about Storm Pattern of Manado, North Minahasa and Minahasa area therefor in design flood analysis still using the Storm Pattern from another area. The aim of this research is to get the Storm Pattern of the Manado, North Minahasa and the Minahasa area. The hourly rainfall data from 2003 to 2014 was taken from the Automatic Rain gage station at Sam Ratulangi airport Station, Maen station, Rumengkor station and Paleloan station. Data was analyzed by using Statistics Methods. The rainfall data that used is the rainfall that has depth more than 50 mm in one rainfall series. Data is analyzed to get the frequency of each rainfall duration and then determine the rainfall duration that can represent the storm pattern of the research area. The result shows that the duration ofÂ  storm pattern of this area is seven to ten hours which 50.83% in first hour, 25.17% in second hour, 8.64% in third hour, 4.93% in fourth hour, 2.93% in fifth hour, 1.35% in sixth hour, 2.43% in seventh hour and 3.72% in eight Â to tenth hour.Keywords: rainfall, pattern